2017
DOI: 10.1016/j.pmcj.2016.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Tangibot: A tangible-mediated robot to support cognitive games for ageing people—A usability study

Abstract: The ever increasing elderly population requires a revision of technology to make it usable and meaningful for them. Most applications take into account their reduced physical and cognitive abilities in order to provide assistive services, but this paper focuses on building technology to improve these capacities through cognitive games. We present Tangibot, a tangible-mediated robot aimed at enabling more intuitive and appealing interactions. A usability study conducted on subjects at three different levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 30 publications
0
26
0
3
Order By: Relevance
“…This category, with 21 articles, is the second most sizable category in this review. Robots represent the technology used most heavily for MCI treatment, with 13 out of 21 articles (Tapus et al, 2009; Chan and Nejat, 2010; Wu et al, 2011, 2013, 2016; Tiberio et al, 2012; Granata et al, 2013; Yamaguchi et al, 2014; Kintsakis et al, 2015; Demetriadis et al, 2016; Reppou et al, 2016; Garcia-Sanjuan et al, 2017; Korchut et al, 2017). On the other hand, papers that consider personal devices and smart environment-based treatment make up 8 out 21: (Zaccarelli et al, 2013; Zuchella et al, 2014; Muscio et al, 2015; Segkouli et al, 2015; Fiorini et al, 2017; Kyriazakos et al, 2017; Manera et al, 2017; Maselli et al, 2017).…”
Section: Application 2: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This category, with 21 articles, is the second most sizable category in this review. Robots represent the technology used most heavily for MCI treatment, with 13 out of 21 articles (Tapus et al, 2009; Chan and Nejat, 2010; Wu et al, 2011, 2013, 2016; Tiberio et al, 2012; Granata et al, 2013; Yamaguchi et al, 2014; Kintsakis et al, 2015; Demetriadis et al, 2016; Reppou et al, 2016; Garcia-Sanjuan et al, 2017; Korchut et al, 2017). On the other hand, papers that consider personal devices and smart environment-based treatment make up 8 out 21: (Zaccarelli et al, 2013; Zuchella et al, 2014; Muscio et al, 2015; Segkouli et al, 2015; Fiorini et al, 2017; Kyriazakos et al, 2017; Manera et al, 2017; Maselli et al, 2017).…”
Section: Application 2: Treatmentmentioning
confidence: 99%
“…In the second example, instead, each participant was involved in the therapeutic use of the robot. Particularly, each participant was asked to perform three different tasks using a tangible-mediated robot: control the orientation of the robot, move the Tangibot from one location to another, and perform a combination of the first two (Garcia-Sanjuan et al, 2017). Contrary to the use of therapeutic robots, the use of a tangible robotic interface is recommended more for people with no or mild cognitive impairments.…”
Section: Application 2: Treatmentmentioning
confidence: 99%
“…In the present motor training approach, by using tangible robots both as game agents and objects to be moved, we aimed to provide an intuitive easy-touse and easy-to-set-up system for motor training. Recent studies showed that utilizing tangible objects that the elderly are familiar with and providing a tangible interface with simplified elements may facilitate learning of using these technologies among elderly (Apted et al, 2006;Hung et al, 2016;Garcia-Sanjuan et al, 2017;Wang et al, 2017;Guneysu Ozgur et al, 2018). Furthermore, making the learning of using these devices easier might be crucial, since the lack of familiarity and the steep learning curve of using training devices may reduce the training efficiency among elderly users (Aarhus et al, 2011;Gerling et al, 2011;Guneysu Ozgur et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, making the learning of using these devices easier might be crucial, since the lack of familiarity and the steep learning curve of using training devices may reduce the training efficiency among elderly users (Aarhus et al, 2011;Gerling et al, 2011;Guneysu Ozgur et al, 2018). Direct contact via touch interfaces is proposed to provide lower cognitive loads and a more suitable and intuitive alternative, especially for aging users (Garcia-Sanjuan et al, 2017;Guneysu Ozgur et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al proposed a tangible gaming board with 64 RGB LED rotary encoders and initial results showed the acceptance of the system by stroke survivors [57]. Direct contact via touch interfaces is proposed to provide lower cognitive loads and a more suitable and intuitive alternative, especially for aging users [20].…”
Section: Introductionmentioning
confidence: 99%